The next christendom The coming of global christianity - Jenkins, Philip (Oxford ; New York Oxford University Press, 2002)
"In looking back over the enormous changes wrought by the twentieth century, Western observers may have missed the most dramatic revolution of all. While secular movements like communism, feminism, and environmentalism have gotten the lion's share of ou
Keywords: Christianity -- Forecasting. Church membership. Christianisme -- Prévision.